①已知a-b=2,ab=2,求ab=2,求a³b-2a²b²+ab³的值?②已知:2x-y=12,x+2y=11,则(2x-y)³-(2x-y)³(x-3y)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:51:29
①已知a-b=2,ab=2,求ab=2,求a³b-2a²b²+ab³的值?②已知:2x-y=12,x+2y=11,则(2x-y)³-(2x-y)
①已知a-b=2,ab=2,求ab=2,求a³b-2a²b²+ab³的值?②已知:2x-y=12,x+2y=11,则(2x-y)³-(2x-y)³(x-3y)
①已知a-b=2,ab=2,求ab=2,求a³b-2a²b²+ab³的值?
②已知:2x-y=12,x+2y=11,则(2x-y)³-(2x-y)³(x-3y)
①已知a-b=2,ab=2,求ab=2,求a³b-2a²b²+ab³的值?②已知:2x-y=12,x+2y=11,则(2x-y)³-(2x-y)³(x-3y)
(1)a-b=2,ab=2
a³b-2a²b²+ab³
=ab(a²-2ab+b²)
=ab(a-b)²
=2×2²
=8
2 2x-y=12.(1)
,x+2y=11.(2)
由(1)得 y=2x-12
把y=2x-12代入(2)得
x+2(2x-12)=11
x+4x-24=11
5x=35
x=7
则y=2x-12=2×7-12=2
所以x=7,y=2
则(2x-y)³-(2x-y)³(x-3y)
=(2x-y)³(1-x+3y)
=12³×(1-7+3×2)
=12³×0
=0
简单解法:由 2x-y=12.(1)
,x+2y=11.(2)
(1)-(2)得
x-3y=1
(2x-y)³-(2x-y)³(x-3y)
=(2x-y)³(1-x+3y)
=(2x-y)³[1-(x-3y)]
=12³×(1-1)
=0
1, ab(a2-2ab+b2)=ab(a-b)2=2*4=8
2,(2x-y)3(1-(x-3y)=12^3*(1-1)=0
a³b-2a²b²+ab³=ab(a^2-2ab+b^2)=ab(a-b)^2=2*2*2=8
³是什么意思?
已知a+b=3,ab=2 求 ab+2ab+ab 的值
已知a-b=,ab=1/8,求-2ab+ab+ab的值
已知ab^2=-2,求-ab(a^2b^5-ab^3-b)的值
已知ab^2=6,求ab(a^2b^5-ab^3-b)的值
已知ab^2=-6,求-ab(a^2b^5-ab^3-b)的值
已知ab^2=6,求ab(a^2b^5-ab^3-b)的值
已知ab^2=6,求ab(ab^3+a^2b^5-b)
已知ab^=2,求-ab(a^2b^5-ab^3-b)的值.
已知ab^2=-6求-ab(a^2b^5-ab^3-b)
已知ab^2=-1,求-ab(a^2b^5-ab^3-b)的值
已知ab²=6,求ab(a^2b^5-ab^3-b)的值
已知a^2b^3=6,求(ab^2)^2*(ab)^3*ab^2
已知a^2+ab=-10,b^2+ab=14,求ab的值~
已知a+b=1/2,ab=3/b求ab+2ab+ab的值
已知a-b=-1,ab=-2,求代数式(3a-4b-ab)-(a-2b+3ab)
已知a-b=2,ab=-1 求(4a-5b-ab)-(2a-3b-5ab)
已知a-b=3ab,求代数式2a-2b-ab/a-b+2ab的值
已知a-b=2ab,求a-3ab-b/2a-ab-2b的值